Infection of Ornithobacterium rhinotracheale (ORT) in chickens in Indonesia - Adin Priadi; Lily Natalia (Indonesian Center for Animal Research and Development (ICARD), 2006)
Ornithobacterium rhinotracheale is a bacterium identified as a new species in 1994 and generally associated with respiratory distress in chickens. From 214 of sinus swabs, tracheal swabs, lungs, airsac, liver heart blood samples and yolk sacs of chickens suffered from respiratory distresses, 6 isolates of O. rhinotracheale were isolated. These isolates were obtained from tracheal swabs of broiler chickens aged between 28-35 days old and broiler breeder of 32 weeks old. Upon incubated on blood agar for 48 hours at 37oC in a 5% CO2 atmosphere, round, convect and grey colonies with diametres of 1-2 mm were observed. The bacteria were pleomorphic, Gram negative rods, negative catalase and positive oxidase. Biochemically, the bacteria did not change potassium nitrate, tryptophan, glucose, arginine, urea, esculin, gelatine, arabinose, mannose, mannitol, N-acetyl-glucosamine, maltose, gluconate, caprate, adipate, malate, citrate and phenyl-acetate in API 20 NE system but β –galactosidase was produced. In the API 20 NE system, the isolates were identified as 0020004, 0060004, 0020104 codes. Tracheitis, air sacculitis, pneumonia and cheesy air sacs were pathological changes generally found in chickens infected with O. rhinotracheale. Trachea is the most important organ for the isolation of O. rhinotracheale. Key Words: Ornithobacterium rhinotracheale, Infection, Chicken, Indonesia